Unraveling the significance of exosomal circRNAs in cancer therapeutic resistance - Kang, Fanhua; Yan, Yuanliang; Liu, Yuanhong; Liang, Qiuju; Xu, Zhijie; Zhu, Wei; Thakur, Abhimanyu (Frontiers in Pharmacology, 2023)
Exosomes are nanoscale extracellular vesicles secreted by a variety of cells, affecting the physiological and pathological homeostasis. They carry various cargoes including proteins, lipids, DNA, and RNA, and have emerged as critical mediators of intercellular communication. During cell-cell communication, they can internalize either by the autologous or heterologous recipient cells, which activate different signaling pathways facilitating malignant progression of cancer. Among different types of cargoes in exosomes, the endogenous non-coding RNAs, such as circular RNAs (or circRNAs), have gained tremendous attention for their high stability and concentration, and playing promising functional roles in the cancer chemotherapeutic response by regulating the targeted gene expression. In this review, we primarily described the emerging evidence demonstrating the important roles of circular RNAs derived from exosomes in the regulation of cancer-associated signaling pathways that involved in cancer research and therapeutic interventions. Additionally, the relevant profiles of exosomal circRNAs and their biological implications have been discussed, which is under investigation for their potential effect on the control of cancer therapeutic resistance.